Role of physiotherapy in relieving osteoarthritis knee pain using Lysholm score - Khatod, Garvit; Butala, Rajendraprasad Ramesh; Das, Sonali (International Journal of Research in Orthopaedics, 2025)
Background: Knee osteoarthritis (OA) is a prevalent condition that significantly impacts quality of life. While pharmacological interventions are commonly used, non-pharmacological approaches like physiotherapy have gained increasing recognition. In this study, the Lysholm Knee Scoring Scale was used to assess how well physiotherapy worked in reducing knee pain and enhancing functional results for people with OA knee. Methods: A randomized controlled trial from 1st February 2023 to 31st July 2023 at Department of Orthopaedics, Padmashree Dr. D.Y. Patil Medical College and Hospital, Nerul, Navi Mumbai, Maharashtra, India was conducted with 500 participants diagnosed with knee OA. Participants were randomly assigned to either the physiotherapy group (n=250) or the control group (n=250). The physiotherapy group received a 12-week standardized program consisting of exercise therapy, manual therapy and education. The control group received standard care. The primary outcome was the Lysholm Knee Scoring Scale, assessed at baseline, 12 weeks (post-intervention) and 24 weeks (follow-up). Secondary outcomes included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), knee range of motion, muscle strength and quality of life. Results: At baseline, the groups were comparable in terms of age, gender, body mass index and clinical characteristics. The physiotherapy group demonstrated significantly greater improvements in the Lysholm Knee Scoring Scale compared to the control group at 12 weeks (mean difference: 10.2, 95% CI: 7.4, 13.0; p<0.001) and 24 weeks (mean difference: 12.2, 95% CI: 9.2, 15.2; p<0.001). Similar patterns were observed for secondary outcomes, with the physiotherapy group showing significant improvements in WOMAC pain and function, knee range of motion, quadriceps strength and quality of life (all p<0.001). Conclusions: This study provides evidence that physiotherapy interventions, including exercise therapy, manual therapy and education, are effective in relieving knee pain and improving functional outcomes in individuals with knee osteoarthritis, as measured by the Lysholm Knee Scoring Scale and other relevant clinical measures.